The Integration of Science-Technology and Living Environment through Islam Religion Education Learning at Adiwiyata-Based Junior High School in Banyumas Regency - Sunhaji, Sunhaji (Dinamika Ilmu, 2018)
Sciences play an important role for human in living their life and technology   constitutes the embodiment of human’s systemic effort in applying the sciences so that it can make things easier and provide wealth for human when it is followed by religion. However, it will bring disaster instead when it is not inspired by religion. One of the destructive impacts of science advancement is environmental crisis. This environmental crisis occurs because of spiritual emptiness, human are far from God. They succumb to greed and keep themselves away from God’s moral guideline and lack ethics in interacting with God’s other creatures. In the academic world, Islam Religion learning constitutes a medium to filter or minimize some human destructive measures to the nature, making the integration of sciences, technology and environment in learning a key to the creation of sciences, technology and environment harmonization.  Using qualitative research with a case study approach, it is expected that the ideal picture of science-technology and living environment sinergy can be obtained. The data are collected using observation, interview and documentation and analyzed using reduction, display and conclusion techniques as well as data verification. The research results indicate that the integration of science-technology and living environment constitutes the highest truth, i.e. the empirical truth which symbolizes the might of Allah, the Almighty Creator, and an effort of synergizing the qauliyah (textual) and kauniyah (universal) verses and of indirectly eliminating the scientific dichotomy. This synergy pattern will never be manifested without Islam Religion Education learning in academic context at schools, particularly Adiwiyata schools which implement the integration pattern of science-technology and environment integrally.